2012
DOI: 10.1152/physiolgenomics.00052.2012
|View full text |Cite
|
Sign up to set email alerts
|

MiR-351 transiently increases during muscle regeneration and promotes progenitor cell proliferation and survival upon differentiation

Abstract: Chen Y, Melton DW, Gelfond JAL, McManus LM, Shireman PK. MiR-351 transiently increases during muscle regeneration and promotes progenitor cell proliferation and survival upon differentiation. Physiol Genomics 44: 1042-1051, 2012. First published September 11, 2012; doi:10.1152/physiolgenomics.00052.2012.-MicroRNAs (miRNAs) regulate many biological processes including muscle development. However, little is known regarding miRNA regulation of muscle regeneration. Murine tibialis anterior muscle was evaluated aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 70 publications
3
43
0
1
Order By: Relevance
“…A previous study observed that miR-351 is transiently increased in early days of muscle regeneration (26). miR-351 inhibits the expression of E2f3, a key regulator of cell cycle progression and proliferation, promotes myogenic progenitor cell proliferation and protects early differentiating myogenic progenitor cell from apoptosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study observed that miR-351 is transiently increased in early days of muscle regeneration (26). miR-351 inhibits the expression of E2f3, a key regulator of cell cycle progression and proliferation, promotes myogenic progenitor cell proliferation and protects early differentiating myogenic progenitor cell from apoptosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…The G0 phase occurs directly before, or concurrently with differentiation. To summarize the process of SC fate specification: Pax3 and Pax7 function to maintain the undifferentiated SC pool, MyoD and Myf5 function as primary myogenic regulatory factors (MRF) to promote myoblast differentiation, and myogenin and MRF4 act as secondary MRFs in terminal cell differentiation (12). …”
Section: Scs In Skeletal Muscle Regeneration: Regulation By Ncrnasmentioning
confidence: 99%
“…38 In addition, Mir351 targets TMEM59 (transmembrane protein 59) 39 and E2f3 (E2F transcription factor 3). 40 Even though Wang et al 41 have proposed that Uvrag might be a potential target gene for Mir351, no study has proven or validated that possibility. Our data show that Uvrag is a direct target of both Mir125a and Mir351 and that EWSR1 deficiency downregulates UVRAG via a miRNA-dependent pathway at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%